Evaluating Socio-Economic and Safety Impacts of Grade-Separated Railway Crossings in Indonesia - Ilham (Ilomata International Journal of Social Science, 2025)
This study analyzes grade-separated rail infrastructure development's socio-economic and safety impacts at railway crossings in Indonesia through Structural Equation Modeling—Partial Least Squares (SEM-PLS). The research examines relationships between safety enhancement, congestion reduction, property values, local business effects, and community support. Data collection involved 450 respondents across six major crossing sites through stratified random sampling using a validated questionnaire (Cronbach's α = 0.89). Results demonstrate significant correlations between safety enhancement and community support (β = 0.678, p < 0.001), traffic congestion reduction (β = 0.623, p < 0.001), and property values (β = 0.589, p < 0.001). The measurement model confirms robust construct reliability (CR > 0.84) and validity (AVE > 0.65), with community support showing strong predictive power (R² = 0.762). Findings indicate that grade-separated crossings reduce accidents while positively impacting property values and business activities. The study contributes to transportation infrastructure theory and provides evidence-based policy recommendations for sustainable development in Indonesia, emphasizing integrated safety measures with socio-economic considerations in infrastructure planning.